Attitudes Toward Crime and Punishment in Vermont: Public Opinion About an Experiment With Restorative Justice, 1999 - Doble, John ([Verlag nicht ermittelbar], 2001)
By the summer of 1998, the Vermont Department of Corrections (DOC) had completed three years of operational experience with "restorative justice," a concept that involves compensating victims and establishing community-based reparative boards that determine how offenders can make amends for their crimes. The purpose of this project was to update the benchmark findings from an earlier survey of Vermont residents in 1994, to assess public attitudes about the reforms and changes that had been instituted by the Vermont DOC, and to explore the possibility of expansion of responsibilities of the reparative community boards. This project involved a telephone survey of a new sample of 601 adult residents of Vermont. The interviewing was conducted on March 15-21, 1999. Respondents were asked a series of trend questions to update the 1994 findings. Respondents were also asked questions about two other programs: the diversion program, in which selected first offenders who fulfilled the terms of a community-based sanction could have their records expunged, and the furlough program, in which offenders making the transition from prison to the community were supervised for an interim period. The survey also explored whether Vermonters would like to see the responsibilities of the reparative boards expanded to include community notification and other types of cases. Residents assessed whether crime in general, violent crime, and illegal drug use had increased compared to five years prior, whether more prisons should be built, whether Vermont's jails and prisons were overcrowded, and whether violent offenders were being released before completing their sentences because of overcrowding. They commented on how often offenders in four scenarios should go to prison and how often they believed that these offenders in fact did go to prison. Respondents rated the performance of various segments of the Vermont criminal justice system and, given 15 offense scenarios, were asked whether the offender should spend time in jail or in community service and rehabilitation. In addition, respondents were asked whether anyone in their household had been a victim of a crime within the last three years and, if so, whether it was a violent crime. Demographic data include sex, employment, education, race/ethnicity, and age category of the respondent, and the county and region where the resident lived.